2015
DOI: 10.2138/am-2015-4961
|View full text |Cite
|
Sign up to set email alerts
|

In-situ oxygen isotope and trace element geothermometry of rutilated quartz from Alpine fissures

Abstract: Finely acicular rutile intergrown with host quartz (rutilated quartz) is commonly found in hydrothermal veins, including the renown cleft mineral locations of the Swiss Alps. These Alpine cleft mineralizations reportedly formed between ∼13.5 and 15.2 Ma (based on ages of rare hydrothermal monazite and titanite) at temperatures (T) of ∼150-450 °C (based on fluid inclusions and bulk quartz-mineral oxygen isotope exchange equilibria), and pressures (P) of 0.5-2.5 kbar (estimated from a geothermal gradient of 30 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…The temperature dependence of the substitution of Zr for Ti in rutile was determined in several studies (Ferry & Watson, ; Shulaker et al, ; Tomkins et al, ; Watson et al, ). We found rutile in one sample (1271B‐5R‐1, 12–14 cm); its Zr contents range from 505 to 1,987 μg/g.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature dependence of the substitution of Zr for Ti in rutile was determined in several studies (Ferry & Watson, ; Shulaker et al, ; Tomkins et al, ; Watson et al, ). We found rutile in one sample (1271B‐5R‐1, 12–14 cm); its Zr contents range from 505 to 1,987 μg/g.…”
Section: Resultsmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T metamorphic conditions or low-grade metamorphic conditions, respectively. Hart et al (2016) demonstrate how the use of mineral inclusions can help constrain pressure, and thus assist in temperature estimates, while Shulaker et al (2015) presented a new calibration at lower temperature ranges combined with oxygen isotopes. Regardless, this has been a useful tool in complementing P-T-t constraints and more studies are needed to tackle these existing difficulties.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The documented occurrence of large crystallographic orientation effects in rutile (Li et al 2010Taylor et al 2012;Schmitt & Zack 2012;Shulaker et al 2015) but not the isostructural cassiterite (this study) indicates that a fundamental difference unrelated to crystallographic structural parameters may contribute to crystallographic orientation effects, During SIMS analyses, the interaction between an incoming ion and a target sample is highly complex, involving numerous variables including the type of primary ion, impact angle and energy, and the composition, bond strength and structure of the sample matrix. Many models for the origin of orientation effects focus predominantly on the crystallographic structure of the target minerals (Huberty et al 2010;Taylor et al 2012;Schmitt & Zack 2012).…”
Section: Causes Of Crystallographic Orientation Effects: Cassiterite mentioning
confidence: 77%
“…Previous studies demonstrated that rutile displays some of the largest effects that have been observed so far (Li et al 2010(Li et al , 2011Taylor et al 2012;Schmitt & Zack 2012;Shulaker et al 2015). Taylor et al (2012) showed that the crystallographic orientation of rutile affects the total signal as measured on the reference mass (Ti3O3 + ), as well as the measured UO2 + /UO + ratio.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation